ANALISIS FAKTOR YANG MEMPENGARUHI LOYALITAS KONSUMEN DI PT. KEBAKKRAMAT ELANG PERKASA - Puji Tri Setyowati; Ida Ayu Kade R K (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
This study aims to analyze the factors that influence consumer loyalty at PT. Kebakkramat Elang Perkasa. The method of data collection was carried out using a questionnaire containing questions related to the research variables and using a simple random sampling technique. The collected data is then processed and tabulated using the data instrument test, classical assumption test, F test, coefficient of determination test, multiple linear regression analysis, and t test. The results of the analysis show that the variables of marketing strategy, product quality, service quality, and customer satisfaction each have a significant positive effect on consumer loyalty.